Investigations into the use of xylopia aethiopica in the treatment of psoroptic mange in rabbits (2001)
Objective: To evaluate the efficacy of Xylopia aethiopica (XA) in the treatment of mange in rabbits. Materials and methods: The efficacy of dried and grounded 30 g and 40 g of XA respectively mixed with 20 ml of palm oil was tested on different sets of mange infested rabbits and this was compared with sulphur, using 80 g of sulphur mixed with 20ml of palm oil. Results: XA was found to be more potent at 40 g relative to 80 g of sulphur, also the rabbits treated with 30 g and 40 g XA’s weight gain during treatment was more significant (p< 0.05) than the control. Conclusion: Our study shows that Xylopia aethiopica exhibits remarkable anti-mange activity against psoroptic mange in rabbits. Further investigations into the isolation of the active constituent responsible for this action is recommended.